2015
DOI: 10.3389/fnhum.2015.00402
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of cerebrospinal fluid free fatty acid levels in patients with acute ischemic stroke

Abstract: In this study, prognostic value of cerebrospinal fluid (CSF) free fatty acid (FFA) levels in patients confirmed with acute ischemic stroke (AIS) was evaluated in a Chinese population. A prospective cohort designed study was conducted at our hospital of the Emergency department from November, 2012 to September, 2014. The National Institutes of Health Stroke Scale (NIHSS) score on admission was applied to assess CSF levels of FFA and specific severity degree of stroke. Evaluation of the prognostic outcomes of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
2
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 33 publications
2
2
1
2
Order By: Relevance
“…Another point of view, our data were not in agreement with Wei et al [ 20 ] and Wang et al [ 19 ] who found a statistical correlation between cardioembolic (CE) stroke and FFA levels in CSF.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Another point of view, our data were not in agreement with Wei et al [ 20 ] and Wang et al [ 19 ] who found a statistical correlation between cardioembolic (CE) stroke and FFA levels in CSF.…”
Section: Discussioncontrasting
confidence: 99%
“…In association with our results, Wei et al [ 20 ] and Duan et al [ 22 ] found that nonsurvivors had significantly higher FFA levels in CSF than survivors with increased risk of death.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Поскольку левокарнитин обладает мощными антиоксидантными эффектами, он оказывает и нейропротективное действие, обнаруженное в исследованиях in vitro, в экспериментах на животных. Так, выявлена прямая корреляция между концентрацией свободных жирных кислот в спинномозговой жидкости и вероятностью развития ишемического инсульта, особенно кардиоэмболического подтипа [44].…”
Section: дисциркуляторная энцефалопатия ишемический инсультunclassified